Revisiting the faithful’s imagination in the light of John Henry Newman and Jean-Luc Marion - Hadrianus Tedjoworo (HTS Teologiese Studies/Theological Studies)
Our common understanding of reason and imagination does not always seem to coincide. In Christianity, and particularly in Catholicism, theology uses rational concepts to account for the truths of faith. While this is natural and necessary, faith knowledge does not come from rational understanding alone. There is a need for some explanation of the ‘reasonableness’ of faith knowledge that the faithful acquires from their experience and that is captured by their religious imagination. This study explores the realness of images captured by the faithful’s imagination and placed within the framework of God’s grace. By revisiting Catholicism, this article sees the faithful’s imagination as a gift from God, and its limits can be found by analysing it phenomenologically in the faithful’s role as witness to the truths of faith. Newman’s concept of real apprehension and Marion’s views on givenness and the turn from subject to witness will be correlated constructively to reveal the realistic features of the appeal of Catholicism. The following analysis provides a theological basis to recognise the layers of religious experience and the faculties in the faithful’s mind that may be valuable to build faith knowledge more comprehensively.